E-LEARNING TRAINING USING EDMODO BASED ON TEACHERS OF SMK NU UNGARAN - Subiyanto Subiyanto; Iin Supriyati; Nisaun Markamah (Jurnal Abdimas, 2018)
Currently, the utilization of information and communication technology has penetrated into all sectors of life. An example of utilization information and communication technology in education is E-learning. The use of e-learning will facilitate students and teachers in the learning process. The purposes of this work are:   to give an explanation of Edmodo utilization in learning process and to provide knowledge on how to apply the features in Edmodo to facilitate the learning process. The target for this devotion is the teachers at SMK NU Ungaran. The methods used in this devotion are lectures and discussions, guidance and training. Lecture and discussion methods are used to convey information relating to Edmodo's theory. Guidance and training are used to directly practice the result of the learned theories. The results that have been achieved in this training are: teachers have understood the role of Edmodo in the learning process and they are able to apply the features that exist in Edmodo to facilitate the learning process.